Adherence to Heart Rate Training Zones in an Exercise Training Program in Adults with Coronary Artery Disease - Gonçalves, Patric Emerson Oliveira (2023)
Objectives: To investigate the effect of exercise intensity on functional capacity in individuals with coronary artery disease, assess adherence to the heart rate training zone (HRTZ), and determine the relationship between trained intensity and functional capacity. Methods: A retrospective study was conducted on the medical records of 54 outpatients with coronary artery disease in a public hospital. The prescribed intensity started at 50%–60% of the heart rate reserve, increasing monthly to 70%–80% by the third month. Spearman’s test was used to assess the correlation between improvement in distance in the incremental shuttle walk test (ISWT), exercise intensity, and rating of perceived exertion (Borg–RPE). Adherence was classified as ‘below’ when HRTZ was not achieved in any phase of the program, ‘intermediate’ when HR was within the HRTZ for one or two months, and ‘above’ when HR was at or higher than HRTZ ≥ two months. Improvement was tested using t-test and one-way ANOVA. Results: 51.9% of participants had an increase in ISWT of ≥70 m (p < 0.0001). In at least one month, 50.9% trained below HRTZ. The trained intensity did not fall below 8.6% of the prescribed HRTZ minimum threshold. Changes in ISWT were not significantly correlated with exercise intensity (p = 0.87) or Borg–RPE (p = 0.16). Conclusion: While a significant increase in functional capacity was found, considerable heterogeneity in changes were observed. This may, in part, be related to adherence to HRTZ with progressive exercise intensity and to the variability in exercise volume in cardiovascular rehabilitation programs.